Active recovery induces greater endurance adaptations when performing sprint interval training - Yamagishi, T.; Babraj, J. (The Journal of Strength and Conditioning Research, 2019)
This study sought to determine effects of recovery intensity on endurance adaptations during sprint interval training (SIT). Fourteen healthy young adults (male: 9 and female: 5) were allocated to 1 of 2 training groups: active recovery group (ARG, male: 4 and female: 3) or passive recovery group (PRG, male: 5 and female: 2). After having completed a 2-week control period, both groups performed 6 sessions of 4- to 6 30-second sprints interspersed with 4-minute recovery over 2 weeks. However, only ARG cycled at 40% VO2peak during the 4-minute recovery periods, while PRG rested on the bike or cycled unloaded. After the 2-week training intervention, both groups improved 10-km time-trial performance to a similar extent (ARG: 8.6%, d = 1.60, p = 0.006; PRG: 6.7%, d = 0.96, p = 0.048) without gains in VO2peak. However, critical power was increased by ARG only (7.9%, d = 1.75, p = 0.015) with a tendency of increased maximal incremental power output (5.3%, d = 0.88, p = 0.063). During the training, active recovery maintained VO2 and heart rate at a higher level compared with passive recovery (VO2: p = 0.005, HR: p = 0.018), suggesting greater cardiorespiratory demands with the active recovery. This study demonstrated that greater endurance performance adaptations are induced with active recovery when performing SIT over a short time frame. The findings of the current study indicate that, with active recovery, individuals can gain greater training benefits without increasing total training commitment time. Further studies are required to determine whether differences are seen with recovery intensity over a longer period.